Leopoldo Sáez Godoy: "El lenguaje secreto de las drogas" en Chile. Yerba, gomas, jale y afines (Santiago, Editorial Universidad de Santiago; 171 págs.) - Matus Olivier, Alfredo (Onomázein, 1996)
no presenta resumen